(untitled) (Bangladesh Journal of Agricultural Research, 2023)
A study was conducted for four consecutive years from 2014 to 2917 at the Regional Horticultural Research Station (RHRS), Bangladesh Agricultural Research Institute (BARI), Lebukhali, Patuakhali. Six mango varieties, viz. BARI Aam-1, BARI Aam-2, BARI Aam-3, BARI Aam-4, BARI Aam-5, BARI Aam-8 developed by BARI and six popular cultivars Khirshapat, Langra, Mallika, Gopalbhog, Fazli and Pahutan were evaluation for their performance. The germplasm were planted in 2010. All the cultivars bloomed in 1st to 3rd week of February. Harvesting time ranged from 2nd week of May to 1st week of July and Gopalbhog and BARI Aam-4 were earlier while Fazli was late season cultivar. In the last year of study (2017), maximum number of fruits per plant was recorded 259 in BARI Aam-3 and minimum 11 in BARI Aam-1. Individual maximum fruit weight was 663.09g in BARI Aam-4 in 2016. Average, individual fruit weight ranged from 553.92 to 183.13g where Fazli was the maximum followed by 465.94g in BARI Aam-4. Minimum individual fruit weight was measured in BARI Aam-3. Total Soluble Solids percent (TSS%) ranged from 16.83 to 21 66% and BARI Aam-3 was maximum and BARI Aam- 2 was minimum. Number of fruits per plant, individual fruit and sweetness (TSS%) of variety/and cultivar fluctuated in different year although the trend of results in the succeeding years was consistent. Bangladesh J. Agril. Res. 46(1): 13-22, March 2021